Fracture performance and numerical simulation of basalt fiber concrete using three-point bending test on notched beam. (20th November 2019) - Sun, Xinjian; Gao, Zhen; Cao, Peng; Zhou, Changjun; Ling, Yifeng; Wang, Xuhao; Zhao, Yawei; Diao, Mushuang
Highlights: The Basalt Fiber greatly improved the peak load and toughness of BFRC. The fracture energy of BFRC had no size effect. The addition of BF could effectively increase the fracture energy of concrete. For notched beams, the initiation toughness increases as the specimen height increases. As BF dosage increases, the initiation toughness of BFRC increases while unstable toughness varies irregularly. Abstract: In this paper, three-point bending tests on precast notched beam and multiscale numerical simulation were used to evaluate and predict the effect of different Basalt Fiber (BF) dosages on the fracture resistance performance for Basalt Fiber Reinforced Concrete (BFRC). The three-point bending test was performed on a series of the notched beams in different sizes and volumetric fiber dosage to obtain the Load-Crack Mouth Opening Displacement (P-CMOD) curves during the loading process. The fracture energy and the double-K fracture parameters were calculated from P-CMOD curves to investigate the influences of fiber volume fraction and beam size on fracture parameters of BFRC. The results indicate that the numerical simulation results are in good coherence with the experimental results. The increase of BF dosage could markedly increase the peak load and the fracture energy of concrete. There was no size effect on fracture energy. Based on the two-parameter fracture theory, the initiation toughness had size effect and increased with the rise of specimen height, while size effect was not significant for unstable toughness. With the augment of fiber dosage, the initiation toughness increased linearly. The unstable toughness varied irregularly with the alteration of fiber dosage but higher than that of ordinary concrete. In addition, this paper developed a homogenization algorithm based on Mori-Tanaka and a multi-scale finite element simulation based on continuum progressive damage theory to evaluate and predict the fracture behavior of BFRC with different sizes and fiber volumetric dosages. The calculated P-CMOD curves from this algorithm were in good agreement with those from experiments and revealed the effects of fiber dosage and size effect on fracture behavior for BFRC.